Effects of distillation cut on the distribution of higher alcohols and esters in brandy produced from three plum varieties1. Issue 1 (14th June 2013) - Spaho, Nermina; Dürr, Peter; Grba, Slobodan; Velagić‐Habul, Esma; Blesić, Milenko
Abstract : The purpose of this investigation was to determinate effects of distillation cuts on the distributions of higher alcohols (1‐propanol, 2‐methyl‐1‐propanol, 3‐methyl‐1‐butanol, 2‐methyl‐1‐butanol, 1‐butanol, 2‐butanol, 1‐hexanol and 1‐pentanol) and esters (ethyl acetate, isopentyl acetate + ethyl lactate, isobutyl acetate, ethyl propionate and ethyl butyrate) in plum brandy. The volatiles were determined by gas chromatography–flame ionization detection. The three most popular plum varieties used in plum brandy (Sljivovica) production, Stanley, Pozegaca and Bilska rana (Buhler), were distilled using a traditional distilling pot and fraction distillation. Three distillation cuts were considered. After separating the head fraction, in the amount of 1.7% of the distilling pot volume, heart fractions were cut at 40, 45 and 50% (v/v) ethanol and tail fractions, analogous to the heart fraction, were collected up to 10% (v/v) ethanol. The ratio of the content of 2‐methyl‐1‐propanol and 3‐methyl‐1‐butanol was 1:1 in the plum brandy produced from Stanley and Pozegaca and the ratio was 2:1 in the plum brandy produced from Bilska rana. This ratio can be used as a 'mark' of variety recognition in plum brandy production. The main differences in the heart fraction were accounted for by the content of the higher alcohols and esters for the distilling cut at 40 and 50% (v/v) ethanol. Copyright © 2013 The Institute of Brewing & Distilling.